MHD Casson fluid flow under the temperature and concentration gradients - S., Parvin; Balakrishnan, N.; M. Isa, S. S. P. (Institute of Physics, University of Latvia, 2021)
This study addresses numerical solutions of a magnetohydrodynamic Casson fluid considering the temperature and concentration gradients. First, two-dimensional partial differential governing equations (PDEs) are considered to develop a mathematical model. Next, similarity variables are applied to modify the PDEs into ordinary differential equations (ODEs). The converted equations are numerically solved with the help of the bvp4c Matlab program. Impacts of the magnetic field and shrinking parameter on the skin friction, Nusselt number and Sherwood number along with the profiles of velocity, temperature, and concentration are displayed through graphs. Finally, the obtained results are validated by comparing with previously published ones. Furthermore, stability analysis is made due to dual numerical solutions to select the stable one, and the first solution is considered stable.